Corrigendum: Mechanism of Rhinovirus Immunity and Asthma, (Front. Immunol, (2021), 12, (731846), 10.3389/fimmu.2021.731846) - Yang, Zuqin; Mitländer, Hannah; Vuorinen, Tytti; Finotto, Susetta (Frontiers in Immunology, 2021)
In the original article, the authors neglected to include the funder Collaborative Research Centre (CRC) 1181 (Erlangen), grant number TP-B08 N to authors Zuqin Yang and Susetta Finotto. In the original article, there was an error. The scientific meaning of the following sentence was unclear owing to poor syntax: “In asthma, are predominantly induced ILC2 producing type 2 cytokine IL-4, IL-5, IL-13, and IL-9”. A correction has been made to Innate Immune Response in Asthma, Innate Lymphoid Cells (ILC2), Paragraph 1. The sentence should read: “In asthma, ILC2 producing type 2 cytokine IL-4, IL-5, IL-13, and IL-9 are predominantly induced”. The same is true of the following sentence: “After RV16 infection, in Tregs were induced both in healthy control and asthmatic subjects with upregulated anti-viral gene expression, such as IFI44L, MX1, ISG15, IRF and STAT1”. A correction has been made to Adaptive Immune Response in Asthma, Treg, Paragraph 2. The sentence should read: “After RV16 infection, Tregs were induced both in healthy control and asthmatic subjects with upregulated anti-viral gene expression, such as IFI44L, MX1, ISG15, IRF and STAT1”. The authors apologize for these errors and state that they do not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2021-12-17
Keywords: asthma; host defense; immune evasion; interferon type I; rhinovirus